The contentious relationship between artificial sweeteners and cardiovascular health - Sandeep Singh; Aditya Kohli; Stuti Trivedi; Sai Gautham Kanagala; F. N. U. Anamika; Nikita Garg; Meet A. Patel; Ripudaman Singh Munjal; Rohit Jain (SpringerOpen, 2023)
Abstract Sweet has always been a fundamental human taste, and while glucose and other kinds of sugar are our primary energy sources, they can also have detrimental effects on health, including weight gain, obesity, cardiovascular diseases, diabetes, and other metabolic diseases. Artificial sweeteners (AS), introduced as sugar substitutes, are a group of chemical compounds that attribute sweetness with almost zero calories and are considered safe for consumption by the Food and Drug Administration (FDA). Although they may help restrict the daily caloric intake of sugar to less than 10% of the daily caloric intake, there are still questions about the long-term safety of AS. A higher risk of hypertension, insulin resistance, high blood sugar, abdominal obesity, and dyslipidemia has been linked to AS. The effect of AS on the cardiovascular system is still unclear, and further research is required. This review examines the potential mechanism of how artificial sweeteners cause cardiovascular diseases.